Optimization of pervaporation separation of bioethanol from direct fermentation of cassava starch - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Hawari, Salma (2009)
Bioethanol separation from dilute fermentation broth is a growing requirement nowadays as its use as a renewable energy source is need of the hour. This investigation aimed at the production of bioethanol in the laboratory scale by undergoing co-culture fermentation in the presence of fungus, Aspergillus niger (AN106) and yeast, Saccharomyces cereviseae using cassava starch as the main substrate. The production of ethanol by direct bioconversion of cassava recorded to 7-9% (v/v). A conventional distillation process was carried out to concentrate ethanol up to 83-89% (v/v) followed by the pervaporation process (membrane separation). A statistical design (central composite design, CCD) was applied to find out the experimental runs of 13 with different values of downstream pressure (1-8 kPa) and initial ethanol concentration (83-89% v/v). The statistical analysis showed that the optimum conditions for high yields of bioethanol separation by a downstream pressure of 8 kPa and an initial feed concentration of 89% (v/v). The highest yield of ethanol separation reached 98.3% (v/v) with a flux of 0.91kg/m2.h and a separation factor of 7.1.